PENGARUH KOMPENSASI, MOTIVASI DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA PEGAWAI PT. JAYA METAL - Lili Supriyadi (ETIKONOMI, 2012)
The purposes of this research are to determine the influence of compensation, motivation, and work characteristics on Work Satisfaction. The analysis method used in this research was Pearson’s correlation analysis and multiple regression analysis with using three predictors. Based on the research, can be concluded as follows there is a significant positive effect of compensation to Work Satisfaction in PT Jaya Metal Jakarta. There is a significant positive effect of motivation on Work Satisfaction. Also, there is a significant positive effect of Work Characteristics on Work Satisfaction. Thus, the overall results of this analysis support the hypothesis that there were significant influences of compensation, motivation, and work characteristics on work satisfaction.DOI: 10.15408/etk.v11i1.1873